#TITLE_ALTERNATIVE# - HERMAWAN (NIM : 12104022); Pembimbing : Dr. Nuhindro Priagung Widodo, ST, MT, FAJAR
Rolling resistance is a factor that influence the fleet productivity. It can be defined as a friction force that occurred due to an interaction between the tire and the road. Several parameters that must be considered in term of computing the rolling resistance value are load weight, velocity, grade of the mine road, California Bearing Ratio (CBR), specific tire, and the tire pressure. The main objective of the particular study is to get the rolling resistance and coefficient rolling resistance value based on some experiments in the laboratory and in the field (PT. Bukit Asam Tbk.) so that the performance of the fleet productivity can be analysed based on the value respectively. In the laboratory the value was measured by a simulation which using winch machine. In the field it was using a car to manually. Based on the laboratory test, the coefficient rolling resistance results is between 0,078-0,132. This test was done by using the material andesite as the road surface. Based on the field experiments which the road surface material made from silt. The results of coefficient rolling resistance can be found as below : - Location hauling road outside pit MTB, range results is 0,027-0,066 - Location specific road at the dumping area of Mahayung, range result is 0,051-0,083 - Location specific road at the front mine Airlaya, range result is 0,065-0,071